Efficacy of febuxostat in hyperuricemic patients with mild-to-moderate chronic kidney disease: a meta-analysis of randomized clinical trials. Issue 13 (March 2018) - Zeng, Xiang Xia; Tang, Yunliang; Hu, Kaixiang; Zhou, Xi; Wang, Jiao; Zhu, Lingyan; Liu, Jianying; Xu, Jixiong
Abstract: Background: To investigate the efficacy of febuxostat in hyperuricemic patients with chronic kidney disease (CKD), relevant randomized clinical trials (RCTs) were analyzed. Methods: We used PubMed, Medline, ISI Web of Science, CBMdisc, and Cochrane Library databases to conduct a systematic literature research. A fixed-effects model was used to evaluate the standardized mean differences (SMDs) with 95% confidence intervals (CIs). We conducted subgroup analysis, sensitivity analysis, and analyzed publication bias, to comprehensively estimate the renoprotective effects of febuxostat in hyperuricemic patients with CKD. Results: Among 296 retrieved studies, 5 relevant RCTs were included in the meta-analysis. The result showed that serum estimated glomerular filtration rate (eGFR) was improved after febuxostat treatment in hyperuricemic patients with CKD, with an SMD (95% CI) of 0.24 [−0.17 to 0.43] and P  = .67 (fixed-effects model). No heterogeneity was observed across studies ( I 2  = 0% and P  = .67). Subgroup analysis suggested that treatment-related reductions in serum eGFR levels were not related to drug doses, intervention times, or region. Conclusions: The present meta-analysis suggests that febuxostat may slow the progression of mild-to-moderate CKD. Given the limited number of included studies, additional large sample-size RCTs are required to determine the long-term renoprotective effects of febuxostat in hyperuricemic patients with CKD.